Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{e,h,f\}$ be the standard basis of the Lie algebra $\mathfrak{sl}(2,k)$. Prove that $(\mbox{ad }e)^3=0$

First I computed $(\mbox{ad }e)(y)$. Let $y=ah+be+cf$, then $(\mbox{ad }e)(y)=[e,y]=ch-ae$. However, I don't really know what $(\mbox{ad }e)^3=0$ means in notation as we only defined $\mbox{ad}$ is not to the power of three.

So anyone got any ideas on what it means and how you actually prove it?

share|cite|improve this question
In general, if $f$ is a function, $f^3=f\circ f\circ f$. In particular, you have $\mbox{ad } e(y)=[e[e[e,y]]]$. – M Turgeon Apr 3 '12 at 17:06
I see you haven't commented on my answer. If you need more clarifications, just tell ;) – M Turgeon Apr 17 '12 at 15:48

Recall the following relations : $[e,f]=h$, $[h,f]=-2f$, and $[h,e]=2e$. Given an element $y=ah+be+df$ of your Lie algebra $\mathfrak{sl}(2,k)$, you first have $$[e,y]=[e,ah+be+df]=a[e,h]+b[e,e]+c[e,f]=-2ae+ch.$$ Continuing on, we have $$[e,[e,y]]=-2a[e,e]+c[e,h]=-2ce.$$ Applying $\mbox{ad }e$ once more gives $$[e,[e,[e,y]]]=[e,-2ce]=0.$$ Therefore, we conclude that $(\mbox{ad }e)^3=0$ (since $y$ was an arbitrary element).

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.